The Influence Of Facilities And Work Environment On Employee Performance At The Mulak Sub-District Of Zfice A Wholebunch Of Cabbage - Nadia Eferiani; Kasinem Kasinem; M. Pahlan (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2026)
This study aims to determine the Effect of Timely Delivery and Online Tracking System (e-tracking) on Customer Satisfaction (a case study of JNE Express service users in Lahat City) both partially and simultaneously.This study is a quantitative associative research using the calculation of the slovin formula in the determination of the sample. The sample used in this study amounted to 77 respondents. Based on the results of the study, the regression equation Y = 6.629 + 0.475 X1 + 0.362 X2+ e, means that without the variables of Delivery Punctuality (X1) and Online Tracking System (e-tracking) (X2), Customer Satisfaction (Y) is 6.629. The value of the determination coefficient (R2) is 0.771, meaning that the independent variables have a contribution with the dependent variable of 77.1% and the remaining 22.9% is influenced by other factors that were not studied by the author. Based on the results of SPSS processing version 25.0, the Fcal value of 124.886 was obtained while the Ftable value was 3.120 thus 124.886 > 3.120, then Ho was rejected and Ha was accepted, meaning that the variables of Delivery Timeliness (X1) and Online Tracking System (e-tracking) (X2) together have a significant effect on Customer Satisfaction (Y). The Ttable value is 1.665. By comparing the value of Thcal and Ttable, it can be concluded: the variable Delivery Punctuality (X1) with the value of Tcal > Ttable or 4.154 > 1.665, then Ho is rejected and Ha is accepted. The Online Tracking System (e-tracking) (X2) with a Tcal value of > Ttable or 3,251 > 1,665, the variables of Delivery Punctuality (X1) and Online Tracking System (e-tracking) (X2) have a partial effect on Customer Satisfaction (Y) (a case study of JNE Express service users in Kota Lahat)